Urgensi Pemilihan Pemimpin Beretika dalam Perspektif Maqashid Syariah Menuju Tatanan Sosial dan Politik yang Sehat - Arif Sugitanata (LP2M Universitas Ibrahimy, 2024)
This research explores the urgency of electing ethical leaders, where the challenges of globalisation and the complexity of contemporary problems make ethical leadership particularly relevant. Using the Maqashid Shariah theoretical framework, this study examines how ethical leaders can contribute to the benefit of the people through the protection of five critical aspects of life: religion, soul, mind, offspring, and property. Utilising desk research involving descriptive-analytical analysis of primary data sources such as books, journals, and relevant websites to comprehensively understand leadership ethics and its application in achieving sharia objectives. The results show that ethical leaders play a crucial role in building a healthy social and political order through fair and responsible policy-making, promoting justice and the common good, strengthening the foundations of democracy, and facing global challenges. In addition, ethical leaders are also crucial in promoting a culture of integrity and accountability, vital for crisis management and combating corruption. From a Maqashid Shariah perspective, the election of ethical leaders supports Islamic principles that favour the development of a just and prosperous society, confirming the relevance of electing ethical leaders not only in the broad political and social context but also within Islam's ethical and moral framework. This research invites stakeholders to adopt a leader selection paradigm that combines professional prowess with moral excellence, opening new insights into the importance of ethical criteria and integrity in leader selection for sustainable development.